EMBRYONIC DEVELOPMENTAL STAGES OF IKAN PALMAS (Polipterus senegalus senegalus) - I Wayan Subamia; Media Fitri Isma Nugraha; Slamet Sugito (Indonesian Aquaculture Journal, 2008)
The purpose of these observations was to identify the stages of the embryo development of ikan palmas (Polypterus senegalus senegalus) and determine the length of duration of each stage. Broodstocks were cultured in aquaria 6 cm x 72 cm x 50 cm in size. The broodstock were stocked at ratio of 1:1 and fed ad libitum with earthworm, small feed fish (ting sea fish) and golden snail. The Palmas broodstocks here naturally spawned in artificial nests made of split plastic raffia in resembling the aquatic plant found in the natural habitat of ikan palmas. After 21 days of culture period, the broodstock began to lay eggs in gradually for 20 days. The average diameter of the eggs was 25 μm. The embryo developed in 24 hours after fertilization and hatched out three days after the embryo had developed.